The Cooperativism And The Constitutional Social Function Of The Cooperation In The Constitutions Of Italy And Brazil - Joelma, Candida (Cooperativismo & Desarrollo, 2020)
The present study aims to demonstrate the foundations of the modern cooperation, always present in human relations since its need for survival. It has to be said that this same cooperation is configured as an existing experience at the heart of world cooperativism, directly linked to its origin, to its constitution as a social movement; however, even more related to its durability and the continuity in the historically perceived economic importance. In addition to this idea, the importance of it in the Italian and Brazilian Constitutions will be highlighted, in particular encouraging cooperation in these countries. Thus, it appears that to cooperate is to work synchronously in pursuit of the same objective; its practice educates, developing in people a participative, human and solidary sense. In this sense, and seeking to face the elements of control of the problem and theoretical frameworks as well as the set of concepts and relationships explored, the work was divided into four items since the introduction, the first part specifically about cooperation itself, the second on the listed Constitutions and finally, the final considerations.Keywords: Brazil; Federal Constitution; cooperation; cooperativism; Italy.
Keywords: Constitutions; cooperation; cooperativism; social function; Brazil; Italy